WEAPONS OF THE TRIBES OF THE NORTHERN PONTIC ZONE IN THE 16TH - 10TH CENTURIES B.C. - Klochko, Viktor (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni., 1993)
The first project of the mutual Polish-Ukrainian studies of the oldest history of the zone of the border of the Eastern and Western part of Europe was started in the 80’s. An outline of a contract of co-operation between Adam Mickiewicz University and the Institute of Archaeology of the Ukrainian Academy of Sciences worked out at that time did not, however, receive an acceptance from the Ministry. This conception could only be taken up again in 1991. One of the elements of a contract drafted at that time is a publication of a series devoted to the prehistorical culture of the communities of a given zone. The Baltic-Pontic Studies are supposed to be a forum for discussions of the oldest — mainly ”pre-ethnic” — history of settlement environments of the boundary of the basins of both seas that are mentioned in the title. Thus, one may observe that this project refers directly to the earlier initiative of Poznan scholars — a periodical Slavia Antiqua. It fills in a great gap in those publications that serve the promotion of archaeology in this part of Europe. Each volume in this series will deal with one subject, giving monographs or collections of articles (commissioned) according to subjects. V.I. Klochko’s mono¬graph that starts the series deals with the North Pontic weapons in the second half of the second millenium B.C. It initiates a cycle of works on the early forms of re¬lations between the two cultural environments in which we are interested, including in particular the beginnings of the organized exchange routes. The support of this initiative to publish a series of works by Committee of Scientific Research marks the first stage of existence of the Baltic-Pontic Studies. We hope that as consecutive volumes appear the range of interests in the problems promoted by the series will extend as well as justification for the further development of the series.
Keywords: Weapons; Pontic zone